How Do European SME Owner–Managers Make Sense of ‘Stakeholder Management’?: Insights from a Cross-National Study - Schlierer, Hans-Jörg (Journal of business ethics, 2012)
The vast majority of empirical research on stakeholder management has traditionally focused on multinational corporations. Only in recent years, scholars have begun to pay attention to the stakeholder management concept in relation to small- and medium-sized enterprises (SMEs). The few existing studies in this area, however, discuss SMEs as a context free category or remain focused on single country analysis. This cross-national empirical research investigates SME owner–managers’ perceptions of stakeholder management in six European countries. The comparative analysis is followed by a discussion of how institutional, cultural and linguistic contexts can influence owner–managers’ sensemaking of stakeholder management. Our study questions the universality of specific management terms and proposes that more attention should be paid to the institutional, cultural and linguistic environments that shape economic activity in different parts of Europe.